Above‐ and below‐ground complementarity rather than selection drive tree diversity–productivity relationships in European forests. (24th May 2021) - Jing, Xin; Muys, Bart; Bruelheide, Helge; Desie, Ellen; Hättenschwiler, Stephan; Jactel, Hervé; Jaroszewicz, Bogdan; Kardol, Paul; Ratcliffe, Sophia; Scherer‐Lorenzen, Michael; Selvi, Federico; Vancampenhout, Karen; et al.
Abstract: Biodiversity experiments have identified both complementarity and selection as important drivers of the relationship between biodiversity and ecosystem functioning. However, their relative importance in above‐ and below‐ground ecosystem compartments of mature forests remains yet to be explored. We adopted a trait‐based approach to partition biodiversity effects in above‐ and below‐ground complementarity and selection. This approach was based on canopy and root traits measured in single‐ and mixed‐species plots in mature forests across a European latitudinal gradient. We assessed the relative importance of above‐ and below‐ground selection and complementarity in driving the relationship between tree species diversity and above‐ground wood production. We used the expected values (based on the values measured in monocultures) of leaf area index (LAI) and fine root biomass as proxies for above‐ and below‐ground selection, whereas canopy packing and rooting depth variability were used as proxies for above‐ and below‐ground complementarity. Our results showed that tree species richness–wood production relationships were driven by above‐ and below‐ground complementarity (i.e. canopy packing and rooting depth variability), rather than selection. The proxies for selection were found to have a positive effect on wood production but were not affected by tree species richness. We concluded that above‐ground‐ but also the largely neglected below‐ground complementarity drives biodiversity–productivity relationships in mature forests. Our findings suggest that choosing tree species with complementary above‐ and below‐ground traits should be considered in afforestation and forest management to promote tree diversity and productivity in European forests. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 摘要: 生物多样性实验将互补(complementarity)和选择(selection)视为生物多样性与生态系统功能之间关系的重要驱动因素。然而，两者在成熟林生态系统地上与地下部分的相对重要性仍待探索。 我们采用了基于功能性状的方法，将生物多样性效应分解为地上和地下互补与选择。该方法主要基于欧洲纬度梯度上在单一物种和混合物种成熟林所测得的冠层和根系功能性状。 我们评估了地上和地下选择与互补对树种多样性与地上木材产量之间关系的相对重要性。我们用叶面积指数(LAI)和细根生物量的期望值(基于单物种样方的观测值计算所得)来表征地上和地下选择，而用冠层堆积和根系深度异质性来表征地上和地下互补。 结果表明，树种丰富度与木材产量的关系是由地上和地下互补(即冠层堆积和根系深度异质性)驱动，而不是由选择驱动。同时发现，表征选择的功能性状(LAI和细根生物量的期望值)对木材生产有积极影响，但不受树种丰富度的影响。 本文的结论是，不仅地上互补，而且被忽视的地下互补也驱动了成熟林生物多样性与生产力的关系。这些发现表明，在造林和森林管理中应考虑选择具有地上和地下互补性状的树种以促进欧洲森林树木的多样性和生产力。 A free Plain Language Summary can be found within the Supporting Information of this article.